2020
DOI: 10.3390/cosmetics7030072
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Insights in Thailand on Usage Satisfaction and Perceived Efficacy of Dexpanthenol in Nappy Care

Abstract: The prevalence of nappy rash or napkin dermatitis in Thailand infants aged 1–24 months is 36.1%. Dexpanthenol-containing nappy creams are clinical validated and effective in treating napkin dermatitis. This study explores the real-world usage satisfaction and perceived effectiveness of a 5% Dexpanthenol-containing product as a preventive strategy for napkin dermatitis. Respondents were mothers with babies between 6–12 months of age, who purchased and used a 5% Dexpanthenol-containing product (Bepanthen® Ointme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Discomfort and distress are common among infants with IDD, [8][9][10][11] and in our study, caregivers reported improvements relief of overnight discomfort, sleep disturbance, and overall discomfort following the application of the product.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Discomfort and distress are common among infants with IDD, [8][9][10][11] and in our study, caregivers reported improvements relief of overnight discomfort, sleep disturbance, and overall discomfort following the application of the product.…”
Section: Discussionsupporting
confidence: 63%
“…Ointment preparations are water‐in‐oil emulsions with high lipid content (over 50% generally) and are the preferred galenic formulation for IDD management. Ointment preparations provide a durable barrier that is effective yet “breathable,” helping to maintain skin hydration while reducing diaper friction 3,8,23 . The efficacy and tolerability of Dexpanthenol‐containing ointment (DCO) have been demonstrated in controlled clinical settings for both treatment and prevention of infant IDD 23–27 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations